Levantamento florístico e etnobotânico como ferramenta ao uso sustentável e conservação dos recursos florestais - Piazza, Eliara Marin (2015)
The forest provides to human society many products and services that are often not appreciated, as in the case of the medicinal potential of forest species. Based on these considerations, the aim of this study was to perform surveys about the medicinal potential of forest species in deciduous seasonal forest remaining in southern Brazil. Floristic-phytosociological evaluations were conducted in the years 2011, 2013 and 2014 in the protected area Quarta Colonia State Park. In the fragment, were installed 25 plots with dimensions of 10 x 10 m where was evaluated the circumference at breast height (CBH) of individuals with ≥ 15 cm, they are members of the vegetation class IV. These plots were further divided into dimensions smaller for survey of individuals measuring between 5,1 ≥ CAP ≤ 14,9 cm (class III), between 1 ≤ CAP ≥ 5 cm (class II), and diameter and height of the soil (DAS) ≤ 1 cm and height (H) ≥ 30 cm (class I). Species richness was verified by the floristic composition. Were calculated the phytosociological descriptors for evaluation of the horizontal structure the forest component. To analyze the diversity we calculated the Shannon index (H'). Semi-structured interviews were conducted with 115 families near the Park. Topics covered included: forest species known for medicinal use, forms of use, results, etc. Were calculated for each species the Use Value of the species, Cultural Value and Relative Importance. Also was determined the Use Value Family Botany and the Consensus factor among informants. In floristic composition were found 63 species belonging to 26 botanical families. The phytosociologic analysis indicated that the highest absolute density was observed in class I, ie 39 970 ind ha-1 at 2014. The highest diversity of Shannon index (H') was found in vegetation class II. The Interviews showed greater use of leaves in medicaments, and consumption in the form of teas. Moreover, were found as the most versatile species for the population Maytenus ilicifolia Mart. ex Reissek and Handroanthus impetiginosus (Mart. ex DC.) Mattos. The botanical family with the highest use value was Celastraceae. Showed greater consensus those particulars relating to the treatment of diseases of the nervous system It can be concluded that some of the species of high ecological importance in the remaining are also important for farmers, and that deciduous seasonal forest remaining have a medicinal potential.